Consensus on domains, formation objectives and contents in cariology for undergraduate dental students in Colombia (2014)
Objective: To achieve a consensus for an undergraduate cariology teaching curriculum between Colombian dental schools in line with the 2015 Global Alliance for a Cavity-Free Future goal: ‘90% of dental schools adopting the current caries paradigm’. Materials and methods: First phase: Four-regional 2-day workshops were conducted with 4 representative teachers (cariology, clinics, basic-science, public health and specialisations) from each of the 24-ACFO schools (Colombian Dental Schools Association) as follows: Presentations: -Main Colombian cariology teaching barriers, -Caries and public health current paradigms; -Schools’ cariology teaching descriptions; -European Cariology Curriculum. Five main-domain subgroup discussions: (i) the knowledge base; (ii) risk assessment, diagnosis and synthesis; (iii) decision-making, preventive non-surgical therapy; (iv) decision-making, surgical therapy; and (v) evidence-based cariology in clinical and public health practice, to adapt domains, objectives and contents to Colombian curriculum, public health and national health system needs. These 4-regional plus 24-school consensuses sent 1 month afterwards were adapted into a preliminary document. 2nd-phase: 10 peer review by national faculty in cariology, and 10 curriculum, basic sciences, research, clinical management and public health experts. School participants and deans reviewed the draft document and suggestions were discussed and adapted into a final consensus document officially presented to the academic community at the ACFO National-Research-Meeting (September, 2012). Results: 24 schools and 92 teachers participated. The Colombian Cariology Curriculum was agreed by 23 schools. It positioned public health into one domain. A general focus on social determination was included, and more relevance was given to fluorosis than erosion. Conclusions: A consensus on cariology teaching for undergraduate dental students was achieved in Colombia and work to promote its adoption has commenced.